8 - Bokk Reviews: Seeds of Famine: Ecological Destruction and the Development Dilemma in the West African Sahel - by Richard W. Franke and Barbara H. Chasin, Montclair, New Jersey: Allanheld, Osmun, - Thomas M. PAINTER (Africa Development, 1982)
Thomas M. PAINTER, Dosso , Niger. Department of Sociology, State University of New York , Binghamton, New York and the Institute for Development Anthropology, Binghamton, New York , USA